In Vitro Antibacterial Effects of Chloroform, Methanol and Water Extracts of Croton Macrostachyus Stem Bark Against Escherichia Coli and Staphylococcus Aureus Standard and Clinical Strains - Minyamer, Tigist; Belay, Getnet (The International Journal of Biotechnology, 2018)
In Ethiopia, different parts of Croton macrostachyus (C. macrostachyus) are used as a traditional medicine to take care of infectious diseases such as typhoid and measles, but there is no documented report on the antibacterial activity of stem bark of this plant in Ethiopia. C. macrostachyus stem bark was extracted using chloroform, methanol, and water extraction solvents and tested for their antibacterial activities against Escherichia coli (E. coli), clinical isolates and standard, and Staphylococcus aureus (S. aureus), clinical isolates and standard, using agar well diffusion and broth dilution methods. The positive control was Chloramphenicol, while dimethyl sulfoxide (DMSO) was served as negative control. The present study showed the potent antibacterial activity of the C. macrostachyus stem bark extract against all tested bacterial pathogens. The methanol extract of C. macrostachyus stem bark showed the highest zone of inhibition (17+1mm) against S. aureus (standard) and the lowest zone of inhibition (12+1) against E. coli (clinical isolate). In this study, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 500 & 500 mg/ml, 62.5 & 125 mg/ml and 250 & 500mg/ml were obtained for water, methanol, and chloroform extracts of C. macrostachyus stem bark against clinically isolated E. coli respectively. C. macrostachyus stem bark extracts have confirmed antibacterial effects, mainly on E. coli and S. aureus. Thus, C. macrostachyus stem bark could be effective for prevention of bacterial infections and may be considered as an option to antibiotic regimens. But further studies should be conducted with different extraction solvents and toxicity and phytochemical analysis must be performed on these plants to use as sources and templates for the synthesis of drugs.